Faktor Utama Penyebab Keterlambatan Proyek Konstruksi Gedung di Bojonegoro - Wafa, Ahmad Waldan Ali; Rodhi, Nova Nevila; Sari, Ayu Kurnia Ratna (Kadiri University, 2024)
Economic development in Bojonegoro is growing rapidly due to massive building construction. However, delays in building construction projects in Bojonegoro are a significant issue because they have a negative impact on costs, efficiency, and local economic stability. Identifying building project delay factors, especially in Bojonegoro, is important because project delay factors may differ from other areas. This research aims to identify and analyze factors influencing building project delays in Bojonegoro. The factors observed include materials, labor, equipment, finance, environment, and design changes. The research uses a quantitative approach and a questionnaire survey method, which has undergone instrument testing on 35 respondents involved in building construction projects in Bojonegoro. The data was tested on classical assumptions and analyzed using hypothesis testing (F and T tests) to determine the effect of each variable on project delays and ranking based on the coefficient values. The research results show that all variables studied significantly influence project delays, with labor as the most dominant factor, followed by environment and finance. Changes in design, equipment, and materials also contribute, although with a smaller impact. This research provides a strong empirical basis for project managers and related parties to develop more effective strategies for managing construction projects, reducing delays, and increasing project efficiency in Bojonegoro.